Samantha Spinner and the spectacular specs - Ginns, Russell 1965- (Delacorte Press, 2019)
"Uncle Paul is still missing. And Samantha just received a new gift from him: a pair of strange purple sunglasses. Are they another powerful present? A clue to his whereabouts? Or just a bad fashion choice? Samantha and Nipper need to figure it out fast, because here comes the SUN!"...